Genome-wide identification and functional prediction of novel and drought-responsive lincRNAs in Populus trichocarpa - Shuai, Peng; Liang, Dan; Tang, Sha; Zhang, Zhoujia; Ye, Chu-Yu; Su, Yanyan; Xia, Xinli; Yin, Weilun (Journal of experimental botany, 2014)
Protein-coding genes are considered to be a dominant component of the eukaryotic transcriptome; however, many studies have shown that intergenic, non-coding transcripts also play an important role. Long intergenic non-coding RNAs (lincRNAs) were found to play a vital role in human and Arabidopsis. However, lincRNAs and their regulatory roles remain poorly characterized in woody plants, especially Populus trichocarpa (P. trichocarpa). A large set of Populus RNA-Seq data were examined with high sequencing depth under control and drought conditions and a total of 2542 lincRNA candidates were identified. In total, 51 lincRNAs and 20 lincRNAs were identified as putative targets and target mimics of known Populus miRNAs, respectively. A total of 504 lincRNAs were found to be drought responsive, eight of which were confirmed by RT-qPCR. These findings provide a comprehensive view of Populus lincRNAs, which will enable in-depth functional analysis.